A battery separator and its preparation method and application

By combining polar nanofibers and hierarchical porous materials on the lithium-ion battery separator to construct a three-dimensional network structure, the problem of short circuits in lithium-ion batteries at high temperatures is solved, the safety and lithium-ion transport capacity of the battery are improved, and the stability and safety of the battery at high temperatures are achieved.

CN120824514BActive Publication Date: 2025-12-05STATE GRID HUNAN ELECTRIC POWER COMPANY LIMITED +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511336736.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-18
Publication Date
2025-12-05
Estimated Expiration
2045-09-18

AI Technical Summary

Technical Problem

Existing lithium-ion battery separators are prone to shrinkage and melting at high temperatures, leading to internal short circuits in the battery. Furthermore, traditional ceramic particle coating materials reduce lithium-ion transport capacity and battery safety.

Method used

A three-dimensional network structure is constructed by combining polar high-temperature resistant nanofibers and alkaline hierarchical porous partially lithiated porous materials to enhance the high-temperature resistance and mechanical strength of the membrane. The hierarchical porous structure also improves the lithium-ion transport capacity, avoids the formation of lithium dendrites, and actively closes the pores at high temperatures to prevent thermal runaway.

Benefits of technology

It improves the high-temperature stability and safety of lithium-ion batteries, prevents lithium dendrite formation, enhances electrolyte wettability, ensures uniform lithium flux, extends battery cycle life, and has the ability to actively stop thermal runaway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a battery diaphragm and a preparation method and application thereof. The diaphragm comprises a porous polymer base film and a functional coating on the surface of the base film, wherein the functional coating comprises a polar nano high-temperature-resistant fiber component, an alkaline multi-stage-pore partially-lithiated porous material, a spherical heat-sensitive component and an auxiliary material. The battery diaphragm prepared by the application has excellent heat resistance, wettability, liquid absorption capacity and lithium ion transmission capacity, can avoid the formation of lithium dendrites, and has the ability of actively stopping thermal runaway through high-temperature closing of pores, so that the electrochemical performance and safety and stability of the battery can be effectively improved when the diaphragm is used in a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a battery separator, as well as its preparation method and application, belonging to the field of new energy battery technology. Background Technology

[0002] Achieving peak carbon emissions and carbon neutrality requires vigorous development of clean and low-carbon energy sources such as wind power and solar power. However, wind power and solar power are characterized by high volatility and randomness, necessitating large-scale energy storage. Lithium-ion batteries are a promising new type of energy storage battery with significant application potential. In 2024, my country's installed capacity of new energy storage reached 43.7 GW, a year-on-year increase of 103%, indicating broad application prospects. However, during long-term operation, lithium-ion batteries are prone to thermal runaway due to internal and external faults, generating large amounts of heat and flammable and explosive gases, leading to fires and explosions. As of 2025, there were over 100 fire and explosion accidents involving battery energy storage systems both domestically and internationally. Therefore, there is an urgent need to develop high-safety, high-performance lithium-ion battery energy storage technologies.

[0003] The separator is a key component of energy storage batteries. It physically isolates the positive and negative electrodes, preventing direct oxidation-reduction reactions between the positive and negative electrode materials, thus ensuring battery safety. Currently, separators mainly use polyolefin-based films such as PE and PP. During battery operation, due to battery design flaws or improper application methods, such as operating at high or low temperatures or high rates, lithium dendrites can form inside the battery. These lithium dendrites can puncture the separator, causing localized short circuits and generating localized high temperatures. Taking PE material as an example, PE material will shrink and melt at a localized temperature of only 130°C. The heated and contracted separator further expands the short-circuit area, ultimately causing the internal short circuit to become unstoppable, inducing large-area short circuits and intense heat generation, leading to violent electrochemical reactions and thermal runaway throughout the battery.

[0004] The key to improving the safety of polyolefin separator materials lies in: (1) improving the thermal stability of the separator; and (2) avoiding the formation of lithium dendrites in the battery. Currently, the most widely used method in industry is to uniformly mix ceramic particles (alumina, boehmite, silicon dioxide, etc.) and binders and coat them on the surface of the polyolefin separator. This method can improve the mechanical strength and high temperature resistance of the separator to a certain extent, but the improvement is limited. It can only keep the separator stable at about 150°C, and this type of separator material cannot actively prevent the safety problems caused by internal short circuits in the battery. At the same time, the alumina, boehmite and other materials currently used do not have rich pore structures, which will lead to a significant decrease in the ability of the separator to pass lithium ions. The permeability generally decreases by more than 50%, which increases the polarization during battery charging and discharging and reduces the battery cycle performance. Another technical approach to improve the safety performance of the separator is to coat the separator surface with a thermosensitive material. When the battery experiences thermal runaway, after the temperature reaches a certain temperature, the thermosensitive material blocks the pores of the separator by melting, thus slowing down the thermal runaway of the battery. This technical approach is theoretically feasible, but in practical applications, due to the thermal inertia when the battery is partially short-circuited, the separator shrinks and melts before the heat-sensitive material can take effect, making it difficult to achieve an effective separator pore-closing effect.

[0005] Therefore, it is of great significance to develop a battery separator that has high stability, good safety performance, and excellent electrochemical performance. Summary of the Invention

[0006] To address the problems existing in the prior art, the first objective of this invention is to provide a battery separator. This separator possesses excellent heat resistance, wettability, liquid absorption capacity, and lithium-ion transport capacity, enabling uniform lithium flux and preventing the formation of lithium dendrites. Simultaneously, through high-temperature pore closure, it has the ability to actively halt thermal runaway, comprehensively improving the electrochemical performance and safety stability of the separator.

[0007] A second objective of this invention is to provide a method for preparing a battery separator. This method is simple, inexpensive, and suitable for industrial production.

[0008] A third objective of this invention is to provide an application of a battery separator. Using this separator in lithium-ion batteries can effectively improve the battery's high-temperature stability, safety performance, and cycle stability.

[0009] To achieve the above-mentioned technical objectives, the present invention provides a battery separator, comprising a porous polymer base membrane and a functional coating on the surface of the base membrane. The functional coating comprises a polar nano-high temperature resistant fiber component, an alkaline hierarchical partially lithiated porous material, a spherical thermosensitive component, and auxiliary materials. The alkaline hierarchical partially lithiated porous material is prepared by alkaline treatment and lithium-ion exchange treatment of a porous matrix material, wherein the porous matrix material comprises an ion-exchangeable molecular sieve material and / or an ion-exchangeable zeolite material.

[0010] First, the functional coating composition of this invention combines high-temperature resistant fibrous materials and granular high-temperature resistant porous materials. Through the entanglement and interconnection of the fibrous materials within the granular materials, a high-temperature resistant three-dimensional network structure is constructed. When the base film is heated, the support provided by the high-temperature resistant materials slows down the shrinkage of the separator, improving its temperature resistance. Furthermore, even at extremely high temperatures, if the base film melts or decomposes, the three-dimensional network structure remains stable due to the excellent high-temperature resistance of both the high-temperature resistant fibrous materials and the high-temperature resistant materials. This maintains the insulation between the positive and negative electrodes, preventing the expansion of short-circuit faults. The high mechanical strength and strong resistance to lithium dendrite penetration of the three-dimensional network structure significantly improve battery safety. Secondly, the polar nano-high-temperature resistant fiber component contained in this invention, due to its high polarity, can improve the overall electrolyte wettability of the separator and reduce the polarization effect during battery charging and discharging. Simultaneously, the mesoporous structure in the partially lithiated hierarchical porous material enhances the coating's liquid absorption capacity, retaining a large amount of electrolyte and increasing lithium-ion transport capacity, i.e., increasing the lithium-ion transference number. Lithium ions are then transported through the microporous structure, achieving uniform lithium flux through the separator, avoiding localized lithium accumulation, and thus preventing lithium dendrite formation. The partial lithiation characteristics of the hierarchical porous material further improve lithium-ion transport efficiency. According to the "Sand time" formula, a high lithium-ion transference number helps slow down lithium nucleation time and prevents lithium dendrite formation. Thirdly, the alkaline effect of the partially lithiated hierarchical porous material neutralizes acidic substances in the battery, preventing gas generation, extending battery cycle life, and achieving excellent battery charge-discharge performance.

[0011] As a preferred embodiment, the excipients include binders, thickeners, dispersants, and wetting agents.

[0012] As a preferred embodiment, the functional coating comprises the following components in parts by weight:

[0013] The polar nano-high temperature resistant fiber component is 1 to 9 parts, more preferably 5 to 8 parts;

[0014] 5 to 20 parts of alkaline hierarchical partially lithiated porous material, more preferably 10 to 20 parts;

[0015] The spherical thermosensitive component is 1 to 10 parts, more preferably 3 to 6 parts;

[0016] 1-4 parts adhesive;

[0017] Thickener 0.05~3 parts;

[0018] Dispersant 0.05~1 part;

[0019] Wetting agent 0.05~1 part.

[0020] By controlling the component content of the functional coating within a specific range, a battery separator with optimal overall performance can be obtained.

[0021] As a preferred embodiment, the lithium-ion exchange rate in the alkaline hierarchical partially lithiated porous material is 10-80%, more preferably 60-80%.

[0022] As a preferred embodiment, the non-lithium ion sites in the alkaline hierarchical partially lithiated porous material include at least one of potassium ion, calcium ion, magnesium ion, strontium ion, and barium ion.

[0023] As a preferred embodiment, the alkaline hierarchical partially lithiated porous material has a particle size of 50 nm to 1 μm and a specific surface area of ​​100 to 800 m². 2 / g, with pore sizes ranging from 0.5nm to 30nm. The macropore size of the alkaline hierarchical partially lithiated porous material is 1–30nm, and the micropore size is 0.5–1nm.

[0024] As a preferred embodiment, the porous matrix material includes ion-exchangeable molecular sieve materials and / or ion-exchangeable zeolite materials.

[0025] As a preferred embodiment, the ion-exchange molecular sieve material includes at least one of silicate molecular sieves, aluminate molecular sieves, aluminosilicate molecular sieves, and phosphoaluminate molecular sieves. The porous matrix material specifically includes 10X molecular sieves, 13X molecular sieves, Y-type molecular sieves, SAPO-34, TS-1, TS-MOR, mordenite, etc.

[0026] As a preferred embodiment, the preparation process of the alkaline hierarchical partially lithiated porous material is as follows: the porous matrix material is soaked in an alkaline solution, followed by the addition of a mixed salt solution containing lithium salt, ammonium salt, and non-lithium alkaline metal salt to conduct a lithium-ion exchange reaction. Alkalinization of the hierarchical porous material enhances its alkalinity. The lithium-ion exchange reaction process constructs a hierarchical porous structure, resulting in a rich composite structure of mesopores and micropores. This enhances the coating's liquid absorption capacity, retains a large amount of electrolyte, and ensures that the membrane can effectively and specifically transport lithium ions.

[0027] As a preferred embodiment, the porous matrix material is dispersed in a solvent, then mixed and stirred with an alkaline solution, followed by solid-liquid separation to obtain an alkali-treated porous matrix material. The mass content of the porous matrix material in the dispersion is 1-50%.

[0028] As a preferred embodiment, the molar ratio of the lithium salt, ammonium salt, and non-lithium alkali metal salt is 6~8:1~2:1~2.

[0029] As a preferred embodiment, the total molar concentration of the lithium salt, ammonium salt, and non-lithium alkali metal salt is 0.1~2 mol / L.

[0030] As a preferred embodiment, the mass ratio of the porous matrix material to the mixed salt solution is 1:1 to 50, and more preferably 1:10 to 50.

[0031] As a preferred embodiment, the concentration of the alkaline solution is 0.1~1 mol / L, the soaking temperature is 20~90℃, and the soaking time is 20~180 min.

[0032] As a preferred embodiment, the lithium-ion exchange reaction is carried out at a temperature of 20~90℃ for a time of 20~180 min.

[0033] As a preferred embodiment, the lithium salt includes at least one of lithium nitrate, lithium chloride, lithium carbonate, lithium phosphate, lithium acetate, and lithium oxalate.

[0034] As a preferred embodiment, the ammonium salt includes at least one of ammonium sulfate, ammonium nitrate, ammonium chloride, ammonium carbonate, ammonium phosphate, and ammonium dihydrogen phosphate.

[0035] As a preferred embodiment, the non-lithium alkaline metal salt is an alkaline earth metal salt.

[0036] As a preferred embodiment, the alkaline earth metal salt includes at least one of calcium sulfate, calcium nitrate, calcium bromide, calcium chlorate, calcium hypochlorite, calcium perchlorate, magnesium nitrate, strontium nitrate, strontium chloride, barium chloride, barium nitrate, and barium acetate.

[0037] As a preferred embodiment, the polar high-temperature resistant nanofiber component includes at least one of acrylic acid-grafted nanocellulose, methacrylic acid-grafted nanocellulose, acrylonitrile-grafted nanocellulose, acrylic acid-grafted aramid fiber, methacrylic acid-grafted aramid fiber, acrylonitrile-grafted aramid fiber, acrylic acid-grafted polyimide fiber, methacrylic acid-grafted polyimide fiber, and acrylonitrile-grafted polyimide fiber. This invention uses acrylic or acrylonitrile-grafted modified fibers, which can improve the polarity of the high-temperature resistant nanofiber component and enhance its hydrophilicity.

[0038] As a preferred embodiment, the polar nano-high temperature resistant fiber component has a length of 1~5μm and a diameter of 10~60nm.

[0039] As a preferred embodiment, the spherical thermosensitive component includes at least one of polyolefin, polyolefin derivative, polyvinylidene fluoride copolymer, polyacrylic acid, polyacrylic acid derivative, vinyl acetate copolymer, paraffin, and polyurethane.

[0040] As a preferred embodiment, the diameter of the spherical thermosensitive component is 100 nm to 2 μm.

[0041] As a preferred embodiment, the adhesive comprises at least one of polyvinylidene fluoride, polyvinyl alcohol, polyvinyl butyral, poly(vinylidene fluoride-hexafluoropropylene), sodium alginate, lithium alginate, polymethacrylic acid, acrylic acid, carboxymethyl chitosan, polyethylene oxide, and styrene-butadiene rubber.

[0042] As a preferred embodiment, the thickener includes at least one of sodium cellulose, lithium cellulose, polyvinylamide, and polyacrylamide.

[0043] As a preferred embodiment, the dispersant includes at least one of lithium polyacrylate, sodium polyacrylate, and ammonium polyacrylate.

[0044] As a preferred embodiment, the wetting agent includes at least one of polyacrylate, polyether-modified silane surfactant, and fatty alcohol polyether wetting agent.

[0045] As a preferred embodiment, the porous polymer-based membrane comprises at least one of polyethylene (PE), polypropylene (PP), polyamide (PA), polyimide (PI), and polyaramid (AR).

[0046] As a preferred embodiment, the porous polymer-based membrane has a thickness of 2~20μm, a porosity of 30~80%, and an air permeability of 10~150sec / 100ml.

[0047] As a preferred embodiment, the thickness of the functional coating is 0.5~4μm, more preferably 1~2μm.

[0048] The present invention also provides a method for preparing a battery separator, which involves coating a mixture containing polar nano-high temperature resistant fiber components, alkaline hierarchical partially lithiated porous materials, spherical thermosensitive components, and auxiliary materials onto the surface of a porous polymer base film and then drying it to obtain the separator.

[0049] As a preferred embodiment, the mixture comprises the following mass percentages:

[0050] The polar nano-high temperature resistant fiber component is 1-9%, more preferably 5-8%;

[0051] The alkaline hierarchical porous partially lithiated porous material comprises 5-20%, more preferably 10-20%;

[0052] The spherical thermosensitive component is 1-10%, more preferably 3-6%;

[0053] Adhesive 1~4%;

[0054] Thickener 0.05~3%;

[0055] Dispersant 0.05~1%;

[0056] Wetting agent 0.05~1%;

[0057] The remainder is water.

[0058] As a preferred method, the drying temperature is 80~130℃.

[0059] The present invention also provides an application of a battery separator as a lithium-ion battery separator.

[0060] Compared with the prior art, the present invention has the following beneficial effects:

[0061] (1) The battery separator of the present invention has strong high temperature resistance and can maintain a complete insulation network at high temperature. It has high mechanical strength and can resist strong lithium dendrite puncture. It has strong wettability, strong liquid absorption capacity, strong lithium ion transport capacity, and uniform lithium flux, effectively avoiding the formation of lithium dendrites. It also has high temperature pore closing capability, which can actively stop battery thermal runaway. It has the ability to neutralize acidic substances and effectively improve the overall charging and discharging performance of the battery.

[0062] (2) The preparation method is simple and the cost is low, making it suitable for industrial production. Detailed Implementation

[0063] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0064] Example 1

[0065] The porous polymer base membrane used is a polyethylene (PE) membrane with a thickness of approximately 9 μm, a porosity of approximately 40%, and an air permeability of approximately 120 sec / 100 ml. The polar nanofiber component used is acrylic acid-grafted nanocellulose, with a length of 3 μm and a diameter of 20 nm.

[0066] The spherical thermosensitive component used is a vinyl acetate copolymer, with a diameter of 600 nm. The binder is acrylic acid (Blue Ocean Black Stone). The thickener is lithium cellulose (Changshu Weiyi). The dispersant is lithium polyacrylate (Blue Ocean Black Stone). The wetting agent is a polyether-modified silane surfactant (Chemadd 6091).

[0067] Acrylic acid grafted nanocellulose: Preparation method reference Probing into the Selective Nucleation Mechanism of Poly(methyl methacrylate) Modified Cellulose Nanocrystals in Enantiomeric Poly(lactic acid) Blends, 2025, 58, 5: 2508–2520.

[0068] Vinyl acetate copolymer: Preparation method reference Self-actuating protection mechanisms for safer lithium-ion batteries, Journal of Energy Chemistry, 2024, 94: 181-198.

[0069] (1) 13X molecular sieve (particle size 500nm, specific surface area 600m²) 2 / g) was dispersed in water to form a dispersion with a solid content of 10%. A 1 mol / L sodium hydroxide alkaline solution was added and stirred and mixed at 80°C for 100 min. The mixture was then filtered to obtain alkali-treated 13X molecular sieve.

[0070] (2) The alkali-treated 13X molecular sieve was added to a mixed aqueous solution of lithium nitrate, ammonium sulfate and calcium sulfate with a total molar content of 1 mol / L. The mixture was stirred and reacted at 90°C for 90 min. The molar ratio of lithium nitrate, ammonium sulfate and calcium sulfate was 8:1:1. After filtration and washing with water, a single-exchange filter cake was prepared. This step was repeated three times to obtain an alkaline hierarchical porous material with a macropore diameter of 20 nm, a micropore diameter of 1 nm, a lithium exchange degree of about 70%, and the remaining non-lithium ion sites were calcium ions.

[0071] (3) Prepare a mixture according to the following mass percentages: 6% acrylic acid grafted nanocellulose, 20% alkaline hierarchical partially lithiumized porous material, 5% vinyl acetate copolymer, 3% acrylic acid, 1% lithium polyacrylate, 1% lithium cellulose, 0.05% polyether modified silane surfactant, and 63.95% water. Stir and mix evenly to prepare a water-based coating.

[0072] (4) The above coating is applied to the base film (polyethylene (PE) separator) using a gravure coating roller. The coating is applied to both sides and then dried (110°C) to obtain a high-safety and high-performance battery separator with a coating thickness of 2 μm.

[0073] This separator was used to assemble lithium-ion batteries, where the positive electrode active material was lithium iron phosphate and the negative electrode active material was graphite. The materials were sequentially assembled into stacks / cores by lamination or winding, and then electrolyte was injected into the cores and sealed. Testing showed that the lithium-ion battery using this separator had a capacity of 280 Ah.

[0074] Example 2

[0075] The battery separator and battery assembly were prepared using the method of Example 1, with the difference that the water-based coating contained 2% polar nano-high temperature resistant fiber component, 20% alkaline hierarchical porous partially lithiumized porous material, 5% spherical thermosensitive component, 3% binder, 1% dispersant, 1% thickener, 0.05% wetting agent and 67.95% water.

[0076] Example 3

[0077] The battery separator and battery assembly were prepared using the method of Example 1, with the difference that the water-based coating contained 6% polar nano-high temperature resistant fiber component, 10% alkaline hierarchical porous partially lithiumized porous material, 5% spherical thermosensitive component, 3% binder, 1% dispersant, 1% thickener, 0.05% wetting agent and 73.95% water.

[0078] Example 4

[0079] The battery separator and battery assembly were prepared using the method of Example 1, with the difference that the water-based coating contained 9% polar nano-high temperature resistant fiber component, 20% alkaline hierarchical porous partially lithiumized porous material, 5% spherical thermosensitive component, 3% binder, 1% dispersant, 1% thickener, 0.05% wetting agent and 60.95% water.

[0080] Example 5

[0081] The battery separator and battery assembly were prepared using the method of Example 1, with the difference being that the polar high-temperature resistant nanofiber composition used was 50% methacrylic acid grafted aramid fiber (DuPont, Kevlar-49) and 50% methacrylic acid grafted polyimide fiber (preparation reference: Nanoporous Low-Dielectric Constant Polyimide Films via Poly(amic acid)s with RAFT-Graft Copolymerized Methyl Methacrylate Side Chains, Ind. Eng. Chem. Res. 2004, 43, 6723-6730).

[0082] Example 6

[0083] The battery separator and battery assembly were prepared using the method described in Example 1, with the difference being that the porous matrix material was a Y-type molecular sieve with a particle size of approximately 600 nm and a specific surface area of ​​approximately 500 m². 2 / g, after modification, the alkaline hierarchical partially lithiated porous material has a macropore diameter of 18nm and a micropore diameter of 0.7~0.8nm.

[0084] Example 7

[0085] The battery separator and battery assembly were prepared using the method of Example 1, except that: ammonium nitrate was used as the ammonium salt, lithium chloride was used as the lithium salt, and calcium nitrate was used as the calcium salt.

[0086] Example 8

[0087] The battery separator and battery assembly were prepared using the method of Example 1, with the difference being that the remaining non-lithium ion sites of the alkaline hierarchical porous material were replaced by magnesium ion exchange, and magnesium nitrate was used as the non-lithium alkaline salt.

[0088] Example 9

[0089] The battery separator and battery assembly were prepared using the method of Example 1, except that sodium cellulose (Lihong) was used as the thickener.

[0090] Example 10

[0091] The battery separator and battery assembly were prepared using the method of Example 1, except that sodium polyacrylate (Blue Ocean Black Stone) was used as the dispersant.

[0092] Example 11

[0093] The battery separator and battery assembly were prepared using the method of Example 1, with the difference being that: the alkaline hierarchical lithiated porous material was exchanged three times, and the lithium ion exchange rate was controlled by controlling the number of ion exchanges and the exchange time; during the exchange process, the lithium content in the porous material was intermittently tested using atomic absorption spectrometry, and the lithium exchange rate of the alkaline hierarchical lithiated porous material was controlled to be 90%, with the remaining non-lithium ion sites being exchanged by calcium ions.

[0094] Comparative Example 1

[0095] The battery separator and battery assembly were prepared using the method of Example 1, with the difference being that the water-based coating contained 20% alkaline hierarchical porous partially lithium-ionized porous material, 5% spherical thermosensitive component, 3% binder, 1% dispersant, 1% thickener, 0.05% wetting agent, and 69.95% water, i.e., non-polar nano-high temperature resistant fiber component.

[0096] Comparative Example 2

[0097] The battery separator and battery assembly were prepared using the method of Example 1, with the difference being that the water-based coating contained 6% polar nano-high temperature resistant fiber component, 5% spherical thermosensitive component, 3% binder, 1% dispersant, 1% thickener, 0.05% wetting agent and 83.95% water, i.e., non-alkaline hierarchical porous partially lithiumized porous material.

[0098] Comparative Example 3

[0099] The battery separator and battery assembly were prepared using the method of Example 1, with the difference that the water-based coating contained 6% polar nano-high temperature resistant fiber components, 20% alkaline hierarchical porous partially lithiumized porous material, 3% binder, 1% dispersant, 1% thickener, 0.05% wetting agent and 68.95% water, i.e., no spherical heat-sensitive components.

[0100] Comparative Example 4

[0101] The battery separator and battery assembly were prepared using the method described in Example 1, with the difference being that the alkaline hierarchical porous partially lithiated porous material was replaced with commonly used alumina material, with a particle size of approximately 500 nm and a specific surface area of ​​10 m². 2 / g.

[0102] Comparative Example 5

[0103] The battery separator and battery assembly were prepared using the method of Example 1, except that the polar high-temperature resistant nanofiber component was replaced with commonly used nanocellulose material with a length of 3μm and a diameter of 20nm.

[0104] Performance tests were conducted on the battery separators and assembled batteries in each embodiment and comparative example, wherein:

[0105] (1) Air permeability test of diaphragm at different temperatures

[0106] Place the diaphragm in an oven at the set temperature for 5 minutes, then cut 3 pieces of the diaphragm, each sample measuring 100mm × 100mm. Place the diaphragm in the test head of an air permeability meter with a suitable test range for air permeability testing, and take the average of the 3 test results as the air permeability of the diaphragm.

[0107] (2) Test of the heat shrinkage performance of the diaphragm

[0108] Mark the longitudinal and transverse lengths of the diaphragm, and measure the longitudinal and transverse lengths of the sample respectively. Then, place the diaphragm flat in a forced-air constant-temperature chamber and maintain it at 180 ℃ for 1 h. Measure the longitudinal and transverse lengths of the sample again, and calculate the thermal shrinkage rate of the diaphragm sample using the formula S(%) = (Di-Df) / Di × 100%, where S is the thermal shrinkage rate and Di is the area of ​​the diaphragm before heat treatment, in mm². 2 Df represents the area of ​​the diaphragm after heat treatment, in mm. 2 .

[0109] (3) Test of the needle penetration strength of the diaphragm

[0110] The diaphragm is fixed in the clamp, and a certain puncture rate (50 mm / min) is set to test the diaphragm puncture strength. After the test, the diaphragm is removed. The thickness at four points around the puncture needle hole is measured according to formula F. P = F0 / d is used to calculate the puncture intensity, where F P 1 is the puncture intensity, in N / μm; F0 is the force measured when the diaphragm is punctured, in N; d is the average thickness of the diaphragm, in μm.

[0111] (4) Battery internal short-circuit performance test

[0112] The blunt needle test method is used to test the cell by squeezing it with a blunt needle with a diameter of 1 / 4 inch until a drop of 500 mV in the cell open circuit voltage is detected, and whether the cell has thermal runaway is recorded.

[0113] (5) Lithium-ion transfer number

[0114] The EIS method was used for testing.

[0115] (6) Electrolyte absorption capacity

[0116] The electrolyte absorption capacity of the membrane material is measured by a method of base membrane liquid absorption in electrolyte.

[0117] (7) Lithium plating test under high-rate charging

[0118] Step 1: Let the battery stand at 25°C for 30 minutes, discharge it to 2.5V at 0.5P, and let it stand at 25°C for 30 minutes.

[0119] Step 2: Charge the battery at 2P constant power to 3.65V, let it stand at 25℃ for 30 minutes, then discharge it at 2P constant power to 2.5V, and let it stand at 25℃ for 30 minutes. Repeat Step 2 100 times to check the lithium plating inside the battery.

[0120] (8) Cyclic performance and energy efficiency test

[0121] Step 1: Let the battery stand at 25°C for 30 minutes, discharge it to 2.5V at 0.5P, and let it stand at 25°C for 30 minutes.

[0122] Step 2: Charge the battery to 3.65V at a constant power of 0.5P, let it stand at 25℃ for 30 minutes, then discharge it to 2.5V at a constant power of 0.5P, and let it stand at 25℃ for 30 minutes. Repeat Step 2 for 1000 cycles, and record the battery's capacity retention rate and energy efficiency after 1000 cycles.

[0123] The capacity retention rate CR (%) after n battery cycles = discharge capacity of the nth cycle / discharge capacity of the first cycle × 100%.

[0124] The specific test results are shown in Table 1.

[0125]

[0126] As can be seen from Table 1, the battery separator prepared by this invention has excellent high temperature resistance, high mechanical strength, can resist strong lithium dendrite puncture, strong liquid absorption capacity, and strong lithium ion transport capacity. When used in lithium-ion batteries, it significantly improves the overall performance of the battery, effectively prevents battery thermal runaway, and enhances battery safety and stability. Comparative Examples 1 and 2 show that when the separator lacks polar nano-high-temperature resistant fiber components or alkaline hierarchical porous lithium-ionized porous materials, the separator shrinkage rate increases significantly, and the material strength and puncture strength decrease significantly. Comparative Example 3 shows that when the separator lacks spherical thermosensitive components, the battery experiences thermal runaway during internal short-circuit testing due to the lack of ability to seal the separator pores in case of failure. Example 11 shows that when the lithium-ion exchange rate of the separator coating material is further increased, the battery's cycle performance is affected. This is because as the lithium-ion exchange rate increases, the calcium-ion exchange ratio decreases, the material's alkalinity decreases, and the ability to suppress the influence of acidic substances during battery cycling decreases, ultimately leading to a relative decrease in cycle performance. Comparative Example 4 shows that when the porous material in the separator coating is conventional alumina, the separator's lithium-ion transference number and liquid absorption capacity are significantly improved. The decrease in electrolyte concentration ultimately reduces the battery's cycle performance and makes it more prone to lithium plating. The mesoporous structure in the multi-level porous material of this invention, with its partially lithiated structure, enhances the coating's liquid absorption capacity, retains a large amount of electrolyte, and increases lithium-ion transport capacity (i.e., increases the lithium-ion transference number). The lithium-ion transference is then achieved through the microporous structure, allowing for uniform lithium-ion flow through the separator, ensuring uniform lithium flux, preventing localized lithium accumulation, and thus avoiding lithium dendrite formation. Comparative Example 5 shows that when the cellulose in the separator coating is a conventional nanocellulose material, the battery's lithium-ion transference number and liquid absorption capacity decrease, leading to reduced cycle performance and increased lithium plating. The polar nano-high-temperature resistant fiber component used in this invention, due to its high polarity, improves the overall electrolyte wettability of the separator, reduces polarization during battery charging and discharging, and increases the lithium-ion transference number of the separator.

[0127] Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A battery separator, comprising a porous polymer base membrane and a functional coating on the surface of the base membrane, characterized in that: The functional coating comprises a polar nano-high temperature resistant fiber component, an alkaline hierarchical porous material partially lithiated, a spherical thermosensitive component, and auxiliary materials. The alkaline hierarchical partially lithiated porous material is prepared by alkaline treatment and lithium-ion exchange treatment of a porous matrix material, wherein the porous matrix material includes ion-exchangeable molecular sieve materials and / or ion-exchangeable zeolite materials.

2. The battery separator according to claim 1, characterized in that: The excipients include binders, thickeners, dispersants, and wetting agents.

3. The battery separator according to claim 2, characterized in that: The functional coating comprises the following components in parts by weight: Polar nano-high temperature resistant fiber component 1-9 parts; 5-20 parts of alkaline hierarchical partially lithiated porous material; 1-10 parts of spherical thermosensitive component; 1-4 parts adhesive; Thickener 0.05~3 parts; Dispersant 0.05~1 part; Wetting agent 0.05~1 part.

4. The battery separator according to claim 1, characterized in that: The lithium-ion exchange capacity of the alkaline hierarchical partially lithiated porous material is 10-80%. The non-lithium ion sites in the alkaline hierarchical partially lithiated porous material include at least one of potassium ion, calcium ion, magnesium ion, strontium ion, and barium ion. The alkaline hierarchical partially lithiated porous material has a particle size of 50 nm to 1 μm and a specific surface area of ​​100 to 800 m². 2 / g, with pore sizes ranging from 0.5nm to 30nm; The ion-exchange molecular sieve material includes at least one of silicate molecular sieves, aluminate molecular sieves, aluminosilicate molecular sieves, and phosphoaluminate molecular sieves.

5. A battery separator according to claim 1, characterized in that: The preparation process of the alkaline hierarchical partially lithiated porous material is as follows: after soaking the porous matrix material in an alkaline solution, a mixed salt solution containing lithium salt, ammonium salt and non-lithium alkaline metal salt is added to carry out a lithium-ion exchange reaction, and the material is obtained.

6. A battery separator according to claim 5, characterized in that: The molar ratio of the lithium salt, ammonium salt, and non-lithium alkali metal salt is 6~8:1~2:1~2; The total molar concentration of the lithium salt, ammonium salt, and non-lithium alkali metal salt is 0.1~2 mol / L; The mass ratio of the porous matrix material to the mixed salt solution is 1:1 to 50; The concentration of the alkaline solution is 0.1~1 mol / L, the soaking temperature is 20~90℃, and the soaking time is 20~180 min; The lithium-ion exchange reaction is carried out at a temperature of 20~90℃ for a time of 20~180 min.

7. A battery separator according to claim 1, characterized in that: The polar nano-high temperature resistant fiber component includes at least one of acrylic acid grafted nanocellulose, methacrylic acid grafted nanocellulose, acrylonitrile grafted nanocellulose, acrylic acid grafted aramid fiber, methacrylic acid grafted aramid fiber, acrylonitrile grafted aramid fiber, acrylic acid grafted polyimide fiber, methacrylic acid grafted polyimide fiber, and acrylonitrile grafted polyimide fiber. The polar nano-high temperature resistant fiber component has a length of 1~5μm and a diameter of 10~60nm; The spherical thermosensitive component includes at least one of polyolefin, polyolefin derivative, polyvinylidene fluoride copolymer, polyacrylic acid, polyacrylic acid derivative, vinyl acetate copolymer, paraffin, and polyurethane. The porous polymer-based membrane includes at least one of polyethylene, polypropylene, polyamide, polyimide, and polyaramid. The thickness of the functional coating is 0.5~4μm.

8. A battery separator according to claim 2, characterized in that: The adhesive includes at least one of polyvinylidene fluoride, polyvinyl alcohol, polyvinyl butyral, poly(vinylidene fluoride-hexafluoropropylene), sodium alginate, lithium alginate, polymethacrylic acid, acrylic acid, carboxymethyl chitosan, polyethylene oxide, and styrene-butadiene rubber. The thickener includes at least one of sodium cellulose, lithium cellulose, polyvinylamide, and polyacrylamide; The dispersant includes at least one of lithium polyacrylate, sodium polyacrylate, and ammonium polyacrylate; The wetting agent includes at least one of polyacrylate, polyether-modified silane surfactant, and fatty alcohol polyether wetting agent.

9. A method for preparing a battery separator according to any one of claims 1 to 8, characterized in that: The mixture containing polar nano-high temperature resistant fiber components, alkaline hierarchical partially lithiated porous materials, spherical thermosensitive components, and excipients is coated onto the surface of a porous polymer base film and then dried to obtain the final product.

10. The application of a battery separator according to any one of claims 1 to 8, characterized in that: As a separator for lithium-ion batteries.

Citation Information

Patent Citations

  • Lithium ion battery capable of blocking thermal runaway stage by stage and preparation method of lithium ion battery

    CN115939516A

  • Battery diaphragm and secondary battery

    CN117438747A